Pengukuran dan Analisis Beban Kerja Pegawai Bandara Hang Nadim - Bambang Hendrawan; Muslim Ansori; Rahmat Hidayat (Politeknik Negeri Batam, 2013)
The objective of this research is obtaining the description of employee workload whereas it will be as consideration to HR development in Hang Nadim Airport, BP Batam. We use NASA-TLX Measurement Method, a subjective assessment method for human workload measurement for collecting and analyzing data. This research carried out for 2 months and it was involving 40 respondents from Airport employees. We were gathering data through web based questionnaire that filled by the respondents, every day during observation period. Based on the measurement and analysis, the results indicate that there is significant over workload that happened at operation and technical department. Mental Workload also was found as the most contribute to the occurrence of over workload employees. The recommendation no directed to add personnel but more effort to keep good condition for the personnel including the regularly training for personnel